Women Role Optimalization In Sharing Moderatic Islamic Ideology - Yuliani, Irma; Zamzambela, Sholahuddin (The Pontianak State Institute of Islamic Studies, 2021)
This research is based on social phenomenology on the issue of radicalism in Indonesia. The underdevelopment of dakwah innovations by moderates has become a great opportunity for radicals in developing radicalism ideologies. Women as individuals who are believed to have a major influence on the development should be able to optimize their role in teaching moderate Islamic ideology. This research is an opportunity study that seeks a model of optimizing women in sharing moderate islamic ideology. Methode tools have a descriptive qualitative approach with literature studies and in-depth interviews. To create an optimization model, this research was developed based on the principles of manhajul fikri, gender theory, women’s psychological theory, and other relevant concepts. This discussion of observations devided into three mains parts, first: the presentation of moderate dakwah and mowen’s work; second: the construction of architectural models to optimize the role of women in sharing moderate islam; third: provisioning as an alternative to equip themselves with moderate islamic values.